Using the G Suite for Education in Language Teacher Education: Benefits and Challenges - Kakouli-Constantinou, Elis (My University, 2021)
Even though research in the use of cloud technologies in the delivery of online courses is expanding, online language Teacher Education remains an unexplored area. This paper reports on the results of a study conducted during spring 2018 and 2019, in which the G Suite for Education was utilised for the delivery of an online Teacher Education course in English for Specific Purposes (ESP) based on social constructivism and connectivism. It specifically focuses on the benefits and the challenges encountered while using some of the core services of the suite. A total of 24 English language educators from different countries participated in the study. Data were collected through questionnaires administered to the participants before the course, the facilitator’s field notes, the participants’ reflective journals, comments on Google Classroom and Facebook Messenger during the course, and focus groups/interviews after the completion of the course. The results of the study revealed that the G Suite for Education may potentially create the appropriate environment and conditions for learning and professional development. The study also revealed many positive aspects of these technologies as well as challenges encountered. At a time when schools, universities and other educational institutions are moving all of their operations online, this paper can prove useful for all educators, especially language teacher educators, who wish to consider using the G Suite for Education in their practices.
Keywords: Online language teacher education; Cloud computing; G suite for education; Social constructivism; Connectivism